A Forming Method and Theoretical Verification of Curvilinear Cylindrical Gears for Adjustable Contact Area - Xuegang Zhang; Yongchun Xie; Pengfei Wang (Jixie chuandong)
To improve the contact performance of curvilinear cylindrical gears，a forming method for adjusting the contact area of tooth surfaces is proposed. Firstly，a basic scheme is established for adjusting the contact area of tooth surfaces，which means the large gear is formed by a double-edged face-milling cutter，and the concave and convex surfaces of the pinion are formed by the outer-edge and inner-edge face-milling cutters，respectively. Secondly，mathematical models of the gear pair are educed based on meshing theory. Then，under assembly errors，mathematical models of contacting and transmission errors are established based on tooth contact analysis （TCA）. Finally，the feasibility of the proposed scheme is verified through 8 sets of examples. The research results show that the proposed forming method is feasible. Adjusting the curvature radius of the cutter can form gear pairs with any length of contact area. A larger tooth surface contact area can improve the mechanical properties of the gear. If tooth surface contact area is too large，it will increase the sensitivity of transmission errors.